Measurement of orientation and distance change using circularly polarized UWB signals - Narbudowicz, Adam (My University, 2022)
The paper proposes methodology to employ circularly polarized UWB signals for simultaneous measurement of orientation and distance changes between transmitter and receiver. The proposed technique uses the rotational Doppler effect on circularly-polarized pulsed communication. The amplitude of a circularly-polarized signal is immune to polarization misalignment in the presence of rotation, however the phase is subjected to a frequency-invariant shift proportional to the rotation angle. This significantly distorts the pulse shape in the time-domain and can be used for the measurement of the rotated angle. By combining the technique with the well-known localization capability of UWB systems, one can precisely measure not only the distance, but also the orientation. This is demonstrated by both numerical and experimental studies presented in this paper.
Keywords: UWB systems; circularly-polarized pulsed communication; Doppler effect; Ultrawideband; Remote sensing; Circular polarization; Localization